The Effect of ESG Disclosure on Risk of Financial Distress: Role of Industry Sensitivity - Liwa, Kezia Hertasneng; Daromes, Fransiskus Eduardus; Asri, Marselinus (Magister Akuntansi - Universitas Atma Jaya Makassar, 2024)
This study aims to investigate the moderating role of industry sensitivity in the influence of environmental, social, and governance disclosures (ESG disclosure) on financial distress risk. The population used are nonfinancial companies listed on the Indonesia Stock Exchange (IDX) in 2019-2021. The sample collection method chosen is the purposive sampling method. With this sample collection method, 849 companies were added to the sample pool. The type of data used in this study are documentary data in the form of annual financial statements and annual reports of companies that are tested using multiple linear regression analysis subgroup method. The results of this study indicate that simultaneously dan partially, environmental, social, and governance disclosures have a positive and significant influence on Altman score. The higher the Altman score obtained indicates the lower the risk level of a firm’s financial distress. In addition, industry sensitivity regarding environmental issues does not moderate the relationship between environmental, social and governance disclosures on financial distress risk. The implications of this study are to provide an overview and consideration for the company in order to increase awareness and responsiveness to the social and environmental aspects surrounding the company and encourage the company to implement good governance practices. Another implication of this research is to provide input for users of financial statements, especially investors, to pay attention to environment, social, and governance disclosure as a consideration in making investment decisions.